2003
DOI: 10.1016/s1537-5110(03)00040-0
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of Soil and Crop Properties for Precision Agriculture for Winter Wheat

Abstract: In a precision farming research project financed by the Belgian Ministry of Small Trade and Agriculture, the methods of precision agriculture are tested on grain fields with a view of implementation of precision agriculture methods in Belgian field agriculture. The project encompasses methods for automatic information gathering on soil and crop and analysis of this data for management of within-field variability. Automatic information capturing is combined with traditional data sources of soil sample analysis … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
18
0
2

Year Published

2006
2006
2011
2011

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 31 publications
(21 citation statements)
references
References 7 publications
1
18
0
2
Order By: Relevance
“…The estimated increase in yield by the VNR treatments was close to zero. The findings have been similar for several other tests of algorithms by for example, Berntsen et al 2006;Vrindts et al 2003, whereas Raun et al (2002 reported variable N application to be profitable.…”
Section: Resultssupporting
confidence: 63%
“…The estimated increase in yield by the VNR treatments was close to zero. The findings have been similar for several other tests of algorithms by for example, Berntsen et al 2006;Vrindts et al 2003, whereas Raun et al (2002 reported variable N application to be profitable.…”
Section: Resultssupporting
confidence: 63%
“…Pedersen, 2002). In addition, several other tests of algorithms showed no increase in yield (e.g., Ebertseder, Gutser, Hege, Brandhuber, & Schmidhalter 2003;Flowers et al, 2003;Hansen et al, 2003;Vrindts et al, 2003). In a review of 17 studies of variable N, P and K application rates by Lowenberg and Swinton (1997) five were unprofitable, six were intermediate and six were profitable.…”
Section: Discussionmentioning
confidence: 98%
“…Jiang & Thelen, 2004;Yang et al 1998;Vrindts et al 2003) have observed significant relations between yield and topography within a field. However, those observed in our study were both positive and negative (data not shown) and there was no general significant interaction between N application and most topographic indices.…”
Section: Discussionmentioning
confidence: 99%
“…Sensors that quantify crop parameters, such as the quantity of the biomass and photosynthesis activity, are already available on the market. Sensors used to evaluate plant stress90, 91 or spectral analysis of the crop canopy parameters92–94 would open the way towards more target‐oriented spraying for crop protection purposes. Smaller treatment units could be achieved in the field95, 96 using these methods.…”
Section: Actionsmentioning
confidence: 99%